Nationalism in the poems selected from Guerilla Flower, 1946 A postcolonial interpretation - Abellar, Archie S. (2003.)
Poetry is a creative form of expressing an opinion with regard to a pressing situation. The poems in the Guerilla Flower were manifestations of the perceptions and aspirations of the Filipinos especially the Ilonggos caught in World War II. The poems were published in Iloilo City after the Ilonggos experienced the turbulent years of the japanese ocupation. For them, the occupation was unforgettable experience that enabled them to affirm nationalism. However, underlying such affirmatin was a tragic flaw, that is, they were compalcent and inclined to sympathize with the Americans while being sarcastic and hostile towards the Japanese, even though these two foreign powers were both colonizers and worthy of condemnation. The realities of Philippine society under war led to distinct Filipino views and actions toward these two colonizers. After the process of distillation of the poems, the elements of nationalism such as language, religion and historical experience were tainted with colonial influences., the use of poetry for historical investigation has a seminal appeal since it maintains the rationale of interdisciplinary-the fusion of literacy criticism and historiography to bring out a better off and encompassing understanding of the complicated nature of present Philippine social reality. The use of postcolonialism as a theoretical tool enables the Filipino people to collocate the object past and present to determine the effects of colonialism for the future.
Thesis (Undergraduate, Bachelor of Arts in History) College of Atts and Sciences, University of the philippines in the Visayas, Miagao, Iloilo.
Keywords: Poems -- Nationalism; Poems -- postcolonial interpretation; Guerilla Flower -- Poem